An Empirical Analysis of Cost Efficiency and Share Performance in Indonesian Banking Industry - Purnama, Gita Prisilfia (2014)
Indonesia is a member of G-20 major economies which has rapid development and is likely to offer new market. It is therefore important to learn and understand Indonesian banking sector. Competitive market has driven banks to deliver higher returns to their shareholders, make the measurements of bank performance and their relationship with the market performance become more crucial. To the authors’ knowledge, this study is the first that estimates the cost efficiency of the listed Indonesian commercial banks using parametric approach (SFA) and links it to their stock price using the very recent dataset (2006-2013) that takes into account the global financial crisis. The empirical results from this study indicate that cost efficiency scores in Indonesian banks deteriorated gradually during 2006 to 2013. With respect to the asset size, large banks are the most cost efficient compared to medium and small banks. While examining the relationship between efficiency and stock returns as the market performance, the regression result suggests that change in cost efficiency is statistically significant and negatively reflected in the stock returns.